Adoption is (not) a Dirty Word: Towards an Adoption-centric Theory of Anishinaabeg Citizenship - Lee, Damien (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2015)
This paper argues that the resurgence of Indigenous peoples’ citizenship orders can be informed in part by tenets of Indigenous customary adoption. The paper considers registration as an Indian under Canada’s Indian Act as having conflated being “Indian” with a Eurocentric property-holder identity, which First Nations now internalize through band membership practices. As such, I argue that adoptees and customary adoption are seen as suspect because they challenge the blood- and property-based conceptions of what it means to be “Indian.” Anishinaabeg customary adoption is taken up here in an analytical approach to re-thinking how citizenship could be discerned in anti-colonial ways; specifically, I consider “caring for others” and the concept of “controlling our associations” in developing an adoption-centric theory of Anishinaabeg citizenship.